Anderson localization of composite excitations in disordered optomechanical arrays. (9th January 2017) - Roque, Thales Figueiredo; Peano, Vittorio; Yevtushenko, Oleg M; Marquardt, Florian
Abstract: Optomechanical (OMA) arrays are a promising future platform for studies of transport, many-body dynamics, quantum control and topological effects in systems of coupled photon and phonon modes. We introduce disordered OMA arrays, focusing on features of Anderson localization of hybrid photon–phonon excitations. It turns out that these represent a unique disordered system, where basic parameters can be easily controlled by varying the frequency and the amplitude of an external laser field. We show that the two-species setting leads to a non-trivial frequency dependence of the localization length for intermediate laser intensities. This could serve as a convincing evidence of localization in a non-equilibrium dissipative situation.